Three Dimensional Electromagnetic Inversion Based on Electric Dipole Source Multiple Locations Excitation - Jianping Li; Ruolong Ma (Institute of Advanced Engineering and Science, 2013)
In this paper, we use integral equation and damped least-squares method to invert three dimensional abnormal body's electromagnetic field through horizontal electric dipole source multiple locations excitation. Multiple groups electromagnetic field data in different excitation and receiving points to be uniform consideration in once inversion, the Jacobian matrix is obtained and divided into linear terms and nonlinear terms. At last, we use the forward simulation data fit the measured data, and gradually modify geoelectricity model parameter values, ultimately achieve optimal fitting, gain three dimensional abnormal body's resistivity. Model test shows that the inversion algorithm has a fast convergence speed, less dependents on the initial value; the inversion result is accurate and reliable. It is an effective solution to the inversion failure caused by insufficient amount of data. DOI: http://dx.doi.org/10.11591/telkomnika.v11i12.3985